Empirical Study on Emotional Perception and Restorative Effects of Suzhou Garden Landscapes: Text Mining and Statistical Analysis - Zhenyu Zhang; Xiaomeng Wang; Mu Jiang (Land)
Suzhou classical gardens, as a unique form of urban green space in China, not only embody rich historical and cultural heritage but also showcase distinctive natural landscapes, exerting a profound impact on modern mental health. This study employs text mining and content analysis methods to qualitatively explore online comments about Suzhou Gardens, which were collected using the Octopus Collector program to mine public reviews from the travel review platform Ctrip. These online reviews were further combined with questionnaire survey data to quantitatively analyze public preferences among different gardens and their restorative experience characteristics. We utilized the ROST CM6 software for high-frequency word extraction, semantic network analysis, and sentiment analysis to reveal the emotional perceptions of the public towards these gardens. The sentiment analysis results indicate that a majority of online comments express positive emotions, frequently mentioning words such as “tranquil”, “quiet”, and “serene”, highlighting the significant psychological comfort these spaces provide. Additionally, through one-way ANOVA and Pearson correlation analysis, we found significant differences in emotional and cognitive dimensions among different gardens, which are closely related to specific spatial factors such as landscape element diversity, visual scale, and types of greenery. These findings suggest that the spatial characteristics of Suzhou Gardens play a crucial role in shaping visitors’ emotional responses. Based on these insights, we proposed a series of design recommendations aimed at enhancing the overall image and healing functions of Suzhou Gardens. The findings of this study not only enrich the theoretical framework of healing landscape design but also provide valuable insights for the practical application of these principles in modern urban green space design. The research underscores the importance of combining functionality with aesthetic elements to meet the psychological needs of contemporary society.